2021
DOI: 10.1111/andr.13119
|View full text |Cite
|
Sign up to set email alerts
|

Berberine ameliorates erectile dysfunction in rats with streptozotocin‐induced diabetes mellitus through the attenuation of apoptosis by inhibiting the SPHK1/S1P/S1PR2 and MAPK pathways

Abstract: Background The population with diabetes mellitus‐induced erectile dysfunction is increasing rapidly, but current drugs are not effective in treating erectile dysfunction. Studies of the traditional Chinese medicine extract berberine on diabetes and its complications provide us with new ideas. Objectives To evaluate the therapeutic effect and potential mechanism of berberine on the erectile function of diabetic rats. Materials and methods Fifty male Sprague‐Dawley rats were randomly grouped, and 42 rats were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Preclinical trials indicated that TCM could improve erectile function by suppressing oxidative stress, curing vascular endothelial injury, inhibiting apoptosis, and anti-atherosclerotic effects. [25][26][27][28] Further research validates that TCM combined with tadalafil has significant efficacy in treating ED with no increase in side effects. 29 Accumulating research focuses on the efficacy of TCM on ED and a systematic evaluation of whether TCM is available as a complementary and alternative therapy is in need.…”
Section: Introductionmentioning
confidence: 76%
“…Preclinical trials indicated that TCM could improve erectile function by suppressing oxidative stress, curing vascular endothelial injury, inhibiting apoptosis, and anti-atherosclerotic effects. [25][26][27][28] Further research validates that TCM combined with tadalafil has significant efficacy in treating ED with no increase in side effects. 29 Accumulating research focuses on the efficacy of TCM on ED and a systematic evaluation of whether TCM is available as a complementary and alternative therapy is in need.…”
Section: Introductionmentioning
confidence: 76%
“…NMN can inhibit apoptosis by reducing the BAX/BCL2 ratio and blocking the cleavage of CASPASE-3 [19]. Similarly, BER reduces apoptosis by suppressing the expression of BAX, which is a pro-apoptotic marker gene, and promoting the expression of BCL2, which is a marker gene of anti-apoptosis [83]. Additionally, COR reduces apoptosis through inhibiting the pro-apoptotic IRE1-JNK pathway [65].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis, resulting from diabetes and nerve damage, is also involved in the pathophysiological process of ED (7,25). The process of fibrosis has also been reported to be involved in aging-related ED (18,23).…”
Section: Discussionmentioning
confidence: 99%
“…As a first-line treatment for ED, the overall effective rate of the phosphodiesterase type 5 inhibitor (PDE5i) is about 87% (7). However, PDE5i is only effective in roughly 65.7% of patients with aging-related ED (8).…”
Section: Introductionmentioning
confidence: 99%